Evaluation of Anti-Bacterial and Anti-Biofilm Efficacy of Lygodium flexuosum (L.) Sw.: An in vitro Study - Rajappan, Rejitha Lalitha; Skaria, Chacko Suju; Sheeja, Amithu Jayakumar (Asian Journal of Biological and Life Sciences, 2025)
Aim: The present study explores preliminary phytochemical analysis, anti-bacterial, and anti-biofilm activities of the leaf methanolic extract of Lygodium flexuosum. Materials and Methods: Soxhlet extraction was done on the powdered leaves of L. flexuosum using methanol as solvent. The secondary metabolites in these extracts was checked following standard protocols. Further, antibacterial activity was assessed against both gram positive and negative bacteria through disc diffusion methods. The activity of methanolic extract against biofilms of the pathogens with the best anti-bacterial activity was done using a modified crystal violet staining method. Results: The preliminary phytochemical study revealed the presence of secondary metabolites like alkaloids, flavonoids, tannins etc which has immense therapeutic applications. The results of anti-bacterial study showed that, the maximum zone of inhibition in methanolic leaf extract of L. flexuosum was shown against the gram-negative bacteria Xanthomonas campestris and in the gram-positive bacteria Listeria monocytogenes. Further, these two strains were used to assess the anti-biofilm assay. The activity was best shown against the biofilm of bacteria X. campestris in comparison with L. monocytogenes. The best reduction in biofilm of these bacteria was observed in higher concentrations of extract that is, 100 and 200 mg/mL. Conclusion: These results suggest that the methanolic extract of Lygodium flexuosum possesses strong antibacterial and anti-biofilm properties, attributed to its diverse phytochemicals. The study highlights the potential of this fern as a natural source of bioactive compounds that could serve as alternative treatments for managing bacterial infections and biofilm-associated complications.
Keywords: Anti-Biofilm activity; Antibacterial activity; Lygodium flexuosum; Methanolic Extract; Natural antimicrobials; Phytochemical analysis